2007
DOI: 10.1021/bi6025193
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Basic Region on Tissue Factor that Interacts with the First Epidermal Growth Factor-like Domain of Factor X

Abstract: Tissue factor (TF) facilitates the recognition and rapid activation of factor X (fX) by factor VIIa (fVIIa) in the extrinsic Xase pathway. TF makes extensive interactions with both light and heavy chains of fVIIa, however, with the exception of a basic recognition site for the Gla-domain of fX, no other interactive-site on TF for the substrate has been identified. Structural and modeling data have predicted that a basic region of TF comprised of residues located at a proper height on the membrane surface to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…The mutations of the residues Lys2092/Phe2093 of the C1 domain and Met2199/Phe2200/Leu2251/Leu2252 residues of the C2 domain have been shown to reduce the binding affinity of FVIIIa co-factor on the PL surface, suggesting that these residues might be responsible for membrane interactions[25]. While a similar data is not available for the role of specific residues of GLA domain involvement in membrane interactions, it has been shown that the GLA domain interacts with FVIIIa light-chain during the tenase complex formation [26]. Our current model shows that the -loop region of the GLA domain is at nearly the same plane of the hydrophobic spikes of the C1-C2 interface.…”
Section: Resultsmentioning
confidence: 99%
“…The mutations of the residues Lys2092/Phe2093 of the C1 domain and Met2199/Phe2200/Leu2251/Leu2252 residues of the C2 domain have been shown to reduce the binding affinity of FVIIIa co-factor on the PL surface, suggesting that these residues might be responsible for membrane interactions[25]. While a similar data is not available for the role of specific residues of GLA domain involvement in membrane interactions, it has been shown that the GLA domain interacts with FVIIIa light-chain during the tenase complex formation [26]. Our current model shows that the -loop region of the GLA domain is at nearly the same plane of the hydrophobic spikes of the C1-C2 interface.…”
Section: Resultsmentioning
confidence: 99%
“…Next, intact control HPCs were incubated with 15 mM sulfo-NHS-SS-biotin, a membrane-impermeable compound that reacts with free amines in proteins, including the side chain of lysine. Previous studies have shown that several lysine residues in the TF molecule are critical for activation of FX by the TF:FVIIa complex, [28][29][30] and sulfo-NHS-SSbiotin was previously used to inhibit surface TF PCA. [31][32][33] Similar to 1H1, sulfo-NHS-SS-biotin significantly reduced FXa generation by intact control HPCs and also dramatically reduced the lysis-dependent increase in FXa generation ( Figure 3C).…”
Section: Tf-dependent Fxa Generation By Intact Mouse Hpcs Occurs Indementioning
confidence: 99%
“…In addition, R37 of FIXa can make a hydrogen bond with either T167 or D204 of TF (Figure 3B). Mutagenesis studies support the role of TF residues R200, K201, T167 and K165 in its interaction with the Gla domain of FXa/FIXa (80-83). Thus, comparable interactions exist between the C-terminal helix of the Gla domains of FXa or FIXa with TF.…”
Section: Molecular Recognition In Tf-induced Coagulationmentioning
confidence: 87%
“…The C-terminal region of TF interacts with the Gla domains of FX/Xa (22,80-83) and FIX/IXa (66,67,69). Further, the Gla domains of FX/Xa (68,70-73) and FIX/IXa (66,69) also interact with the Gla domain of FVIIa.…”
Section: Molecular Recognition In Tf-induced Coagulationmentioning
confidence: 99%